Validitas Modul Pembelajaran Berbasis Inkuiri pada Materi Pengelolaan Zakat Untuk Peserta Didik Kelas X SMA - Vitrah Rahmadani; Wirdati Wirdati (ISLAMIKA, 2022)
This study aims to produce inquiry-based learning modules on zakat management materials for class X SMA/MA students and determine the level of validity of the resulting modules. This study uses research and development methods (Reserarch and Development) while the model used is a 4-D model, which consists of four stages, namely define (define), design (define), develop (development), and disseminate (dissemination). However, this research procedure is only carried out until the develop stage. The research subjects consisted of one expert lecturer in the field of Indonesian, one expert lecturer in the field of Fine Arts and one expert lecturer in the field of Islamic Religious Education. The data collection instrument used was a validity sheet. The results show that the inquiry-based learning module on zakat management material for SMA/MA class students is declared eligible after being validated by experts with a percentage of 86.66% with a very valid category.